Peningkatan Asertivitas Siswa yang Diasuh oleh Ibu Single Parent melalui Bimbingan Kelompok - Fadila Afriani; Alizamar Alizamar (Jurnal Neo Konseling, 2019)
This study aims to describe the level of assertiveness of students cared for by single parent mothers before and after being given group guidance services. This study uses a quantitative method with an experimental approach type The One-Group Post-Test Design Pre-Test. The research subjects were students who were cared for by single parent mothers at SMK Negeri 9 Padang totaling 10 people. The data collection technique uses a questionnaire with a Likert scale model. Data were analyzed using the Wilcoxon Signed Ranks Test formula. The research findings revealed that the assertiveness of students cared for by single parent mothers before being given group guidance was in the moderate category with a percentage of 72.16% and after being given group guidance services the results of the posttest were in the moderate category with a percentage of 89.8%. This revealed that there were differences in the level of student assertiveness before and after being given group guidance services. With the findings of these studies BK teachers can continue to improve and develop guidance and counseling services, especially group guidance services to help improve the assertiveness of other students.